ANALISIS PENGGUNAAN BAHASA INDONESIA DALAM IKLAN PRODUK KOSMETIK DI TIKTOK TERHADAP DAYA TARIK KONSUMEN - Devi Mariyani; Sindi Qurotul Uyun; Sugiarti Sugiarti (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The purpose of this study is to evaluate how the use of Indonesian language in cosmetic advertisements on the TikTok application affects customer attraction. Indonesian, as the official language used by most Indonesians, is very important for building successful relationships between sellers and buyers, especially in digital marketing. The method of data collection is to thoroughly look at user ratings and comments on cosmetic product promotional videos on TikTok. The number of likes or comments, as well as the language patterns used in the content and user responses, especially those using Indonesian, are recorded to obtain data. To get a better picture, several additional criteria are also examined, such as the number of views and engagement rate. The results of the study indicate that using formal, clear, and innovative Indonesian in product descriptions, reviews, and promotions can increase customer trust and comfort and have a positive impact on their level of interaction. These results strengthen the theory of marketing communication and consumer perception, which states that marketing content with the right language can increase consumer loyalty and strengthen brand image. In addition, this study provides deeper insight into language-based marketing tactics in e-commerce, especially on TikTok, and offers suggestions on how to optimize local communication to support business success.